Blockchain architecture adoption in supply chain management: A dematel-based analysis of critical factors - Jankin, Abdul Rahman; Ooi, Hai Lee; Lee, Chia Kuang (Growing Science Ltd., 2025)
The uprising of blockchain technology has recently become a trend owing to its prowess to reform the governance of supply chains, offering improved levels of data transparency, traceability, and efficient workflow. The objective drawn on this research is to examine the key determinants that impact the adoption as well as applicability of blockchain technology within the supply chain management context. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) model is tested in this study to inspect and fathom the complex relationships between these components, thereby uncovering their respective significance and interrelationships. The results derived from this study contribute vital insights into the ever-changing landscape of blockchain adoption, with a particular focus on key factors comprising technical competencies, IT infrastructure, interoperability, compatibility, and complexity. The research based on DEMATEL methodology reveals both direct and indirect influences, facilitating a more comprehensive comprehension of these crucial variables. This study is an invaluable resource for industry stakeholders, policymakers, and organizations seeking to embrace blockchain technology into supply chain operations. This study’s original intent is to frame an extensive analysis of the key aspects and their interrelationships, offering valuable insights for making well-informed decisions. The overarching aim is to facilitate the seamless assimilation of blockchain architecture into supply chain management systems, promoting effectiveness along with harmony.